Uptake patterns of critical metals in alpine plant species growing in an unimpaired natural site. (January 2022) - Fehlauer, Till; Collin, Blanche; Angeletti, Bernard; Santaella, Catherine; Dentant, Cedric; Chaurand, Perrine; Levard, Clement; Gonneau, Cedric; Borschneck, Daniel; Rose, Jérôme
Abstract: The range of metals used for industrial purposes - electrical engineering, solar panels, batteries - has increased substantially over the last twenty years. Some of these emerging metals are the subject of geopolitical conflict and are considered critical as their unique properties make them irreplaceable. Many of these elements are poorly studied and their biogeochemical cycles still raise many questions. Aim of this study is to analyse the soil-to-plant transfer of some of these chemical elements and to shed light on their uptake pathways. For this purpose, the geological site of Jas Roux (France) was chosen as this alpine site is naturally rich in critical and potentially toxic elements such as As, Sb, Ba and Tl, but nevertheless is host to a high diversity of plants. Elemental concentrations were analysed in the topsoil and in 12 selected alpine plant species sampled in situ. Statistical tools were used to detect species dependent characteristics in elemental uptake. Our analyses revealed accumulation of rare earth elements by Saxifraga paniculata, selective oxyanion absorption by Hippocrepis comosa, accumulation of Tl by Biscutella laevigata and Galium corrudifolium and an exclusion strategy in Juniperus communis . These findings advance our understanding of the environmental behaviour of critical metals and metalloids such as V, As, Y, Sb, Ce, Ba and Tl and might bare valuable information for phytoremediation applications. Graphical abstract: Image 1 Highlights: Critical metals: a need to understand their biogeochemical cycles. Field-study of a plant community exposed to a natural cocktail of metals(loids). Multivariate analysis of elemental concentrations revealed species related uptake. S. paniculata and H. comosa accumulating a different set of critical metals. Observation of possible links in the soil/plant transfer of Mo/V/Fe and Y/Ba/Ca.